2006
DOI: 10.1161/01.atv.0000221231.56617.67
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Phospholipase A2Group V

Abstract: Objective-To study the distribution of group V secretory phospholipase A 2 (sPLA 2 ) in human and mouse lesions and compare its expression by human vascular cells, its activity toward lipoproteins, and the interaction with arterial proteoglycans (proteoglycans) with those of sPLA 2 -IIA. In addition, we also investigated the effect of a Western diet and lipopolysaccharide challenge on the aortic expression of these enzymes in mouse models. Methods and Results-Immunohistochemistry showed sPLA 2 -V in human and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 42 publications
0
38
0
1
Order By: Relevance
“…ApoB may be particularly susceptible to modification by lipid peroxides inside hepatocytes, both because it would be assembled into close contact with them and because the unique structure of apoB facilitates its aggregation under a wide range of physiologic (e.g., Figs. 1 and 2), pathogenic, and even artificial stimuli that do not affect other proteins to the same extent (4,(42)(43)(44)(45)(46)(47). Its remarkable susceptibility to aggregation allows a normal hypolipidemic response to dietary PUFAs and other stimuli ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ApoB may be particularly susceptible to modification by lipid peroxides inside hepatocytes, both because it would be assembled into close contact with them and because the unique structure of apoB facilitates its aggregation under a wide range of physiologic (e.g., Figs. 1 and 2), pathogenic, and even artificial stimuli that do not affect other proteins to the same extent (4,(42)(43)(44)(45)(46)(47). Its remarkable susceptibility to aggregation allows a normal hypolipidemic response to dietary PUFAs and other stimuli ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it was reported that syndecan-4 controls uptake of modified LDL by group V sPLA 2 (45). The overall mechanism of sPLA 2 in foam cell formation is suggested to comprise modification of lipoproteins (46,47) or sPLA 2 -hydrolyzed lysophosphatidylcholine (LPC) (48). However, our results show that LPS-induced iPLA 2 ␤ activation increases Nox1 expression, thereby increasing ROS production and that foam cell conversion eventually occurs with the cotreatment of LPS and LDL.…”
Section: Discussionmentioning
confidence: 99%
“…3 This increase can be explained by the fact that LDL aggregates contain many copies of apoB-100, and, being multivalent, have the potential to interact with proteoglycans via more ionic interactions than their nonaggregated, native-sized counterparts. Interestingly, binding of LDL to proteoglycans promotes PLA 2 -induced aggregation and fusion of LDL particles, 22 and an enhanced interaction of sPLA 2 -V-treated LDL to proteoglycans has been demonstrated by Rosengren et al 15 In terms of atherogenesis, the full repertoire of the ApoB-100 -containing lipoproteins enter the arterial intima and become entrapped within the subendothelial proteoglycan meshwork. A subendothelially located macrophage synthesizes and secretes sPLA 2 -V, which hydrolyzes the phosphatidylcholines on the surface of the entrapped lipoproteins.…”
Section: See Page 600mentioning
confidence: 91%
“…In contrast, sPLA 2 -V has been shown to efficiently hydrolyze native LDL. 14,15 Most importantly, sPLA 2 -V is able to hydrolyze lipoproteins in complete serum, 15 a finding indicative of the absence of natural inhibitors of the enzyme in serum, and also suggesting their absence in interstitial fluids, such as the intimal fluid, which are derivatives of blood plasma. Thus, the enzyme may also be able to act on lipoproteins in the arterial intima.…”
Section: See Page 600mentioning
confidence: 99%
See 1 more Smart Citation